Restorative Justice as an Alternative for The Settlement of Corruption Crimes That Adverse State Finances in The Perspective of The Purpose of Conviction - Sahuri Lasmadi; Elly Sudarti (Fakultas Hukum Universitas Mataram, 2021)
This research was motivated by the rampant corruption crimes committed by state officials. The problem is that the restoration of the state’s financial losses due to the corruption crimes with the current system has not met a profitable solution. This research was doctrinal with a normative legal research method, which was a legal research method based on the statutory and conceptual approaches using analytical descriptive analysis. Settlement of corruption crimes concerning state financial losses is currently carried out through a criminal justice system that priorities a retributive justice approach so that it does not achieve the objective of punishment of un optimal returns to state financial losses. Therefore, a new settlement concept is needed. The concept of restorative justice focuses more on the settlement of criminal cases by emphasizing restoration to its original state, not retaliation. Restorative justice also fulfills the value of justice and legal benefits in order to meet the value of legal certainty. In the future, it is necessary to formulate specific regulations regarding the concept of restorative justice in resolving corruption crimes concerning losses on state finances.